(untitled) (Sains Humanika, 2017)
The purpose of this study is to identify differences in the results of the semester examinations for the Human Biology subject of the Diploma in Medical Laboratory Technology (DMLT) program for science and non-science stream students at the Sijil Pelajaran Malaysia (SPM) level as well as the achievement of male and female students. Furthermore, this study is also intended to predict the results of the Human Biology subject based on the SPM subjects of Biology and Chemistry. This study is a quantitative study involving the analysis of students’ Human Biology subjects for the July-December 2012 session using multiple regression analysis with SPM results as independent variables. The sample used was 40 students who were randomly selected from the College of Medical Laboratory Technology, Kuala Lumpur, and the Allied Health Science College, Kuching, Sarawak. The results of the data analysis showed that the achievement of students from the science stream in the Human Biology subject was better (p<0.05; t=-3.653; df=38) than students from non-science streams and the difference in achievement was significant at 95% confidence level. At the same time, the achievement of female students showed better results (p<0.05; t=-2.082; df=38) as compared to male students. Pearson correlation analysis showed a very strong positive correlation for Biology (r=0.632 (39), p<0.05) and Chemistry (r=0.678 (39), p<0.05) subjects grades to Human Biology subject scores. Linear multiple regression analysis showed that the combined grades of Biology and Chemistry subjects at the SPM level predicted 49.1% of the Human Biology subject scores variant at DMLT level. The implication of this study suggests that candidates from the science stream with better grade results especially in Biology and Chemistry subjects at the SPM level should be given priority for the enrolment to the DMLT program. Since the DMLT program cannot be exclusively offered to female candidates even though the female group is able to achieve better results, male candidatesâ€™ enrolment need to be continued. However, more attention should be given to the male students especially during the learning session of Human Biology subject. Â